Microleakage and shear bond strength of composite restorations under cycling conditions - Zanatta, R. F. [UNESP]; Lungova, M.; Borges, A. B. [UNESP]; Torres, C. R.G. [UNESP]; Sydow, H. G.; Wiegand, A. (Operative Dentistry, 2017)
Objectives: The aim of this study was to evaluate microleakage and shear bond strength of composite restorations under different cycling conditions. Methods and Materials: Class V cavities were prepared in the buccal and lingual surfaces of 30 human molars (n=60). A further 60 molars were used to prepare flat enamel and dentin specimens (n=60 each). Cavities and specimens were divided into six groups and pretreated with an adhesive (self-etch/Clearfil SE Bond or etch-and-rinse/Optibond FL). Composite was inserted in the cavities or adhered to the specimens' surfaces, respectively, and submitted to cycling (control: no cycling; thermal cycling: 10,000 cycles, 5 °C to 55 ° C; thermal/ erosive cycling: thermal cycling plus storage in hydrochloric acid pH 2.1, 5 minutes, 6 × /day, 8 days). Microleakage was quantified by stereomicroscopy in enamel and dentin margins after immersion in silver nitrate. Specimens were submitted to shear bond strength testing. Statistical analysis was done by two-way analysis of variance and Kruskal-Wallis tests (p < 0.05). Results: Microleakage in enamel margins was significantly lower in the control group compared with thermal cycling or thermal/erosive cycling. Erosive conditions increased microleakage compared with thermal cycling (significant only for Clearfil SE Bond). No significant differences were observed in dentin margins. Bond strength of enamel specimens was reduced by thermal cycling and thermal/erosive cycling when Clearfil SE Bond was used and only by thermal/erosive cycling when Optibond FL was used. No differences were observed among dentin specimens. Conclusions: Thermal/erosive cycling can adversely affect microleakage and shear bond strength of composite resin bonded to enamel.